Detection and prevention of IoT-based DDoS attack on IPv6 / Mohammad Ihtisyamuddin Mohd Zaidi - Mohd Zaidi, Mohammad Ihtisyamuddin (2021)
The internet of things (IoT) has been continually growing in the last couple of years, and with the issues of IPv4 address exhaustion, many IoT devices started to adopt IPv6 protocol. These IoT devices appeared to be vulnerable to many kinds of attacks. Attackers can turn these smart devices into botnet to conduct Distributed Denial of Services (DDoS) attacks. Currently, there is no DDoS prevention mechanism able to address IoT-based DDoS attacks using the IPv6 protocol. To address this threat, this paper proposed a solution using Python mitigation script that can detect DDoS attack by collecting data from system parameters such as CPU, memory, and network utilization. The proposed solution also provides a DDoS attack prevention mechanism using the Ubuntu default firewall configuration tool, Uncomplicated Firewall (UFW). The result from the mitigation test shows that the system is effective against DDoS attack on IPv6. This project seeks to help network administrators and smart homeowners to prepare and reduce the risk of being a victim of IoT-based DDoS attacks